Oil and gas layer protective agent using high-performance resin and fiber as raw materials and preparation method thereof

By using a network structure constructed of high-performance resin and composite fibers as a protective agent for oil and gas layers, it solves the problems of limited improvement in plugging effect and damage to the reservoir in the existing technology, and achieves a more efficient plugging effect and better stability. sex.

CN118995160BActive Publication Date: 2025-01-24CHENGDU BAIN PETROLEUM TECH SERVICE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411495916.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The prior art has limited improvement in sealing oil and gas layers, and it is difficult to penetrate deep into the hole and throat to plug leakage in harsh environments, and commonly used particles are prone to damage the reservoir.

Method used

A network structure constructed of high-performance resin and composite fiber is used as a protective agent for the oil and gas layer. The composite fiber is composed of inner and outer fibers. The inner fiber is polyglycolic acid, and the outer fiber is polylactic acid@carboxymethylcellulose sodium. The resin contains silicone and polyvinyl alcohol, and introduced through dopamine modification and boric acid to improve stability and blocking effect.

Benefits of technology

It achieves a more efficient plugging effect and reduces damage to the reservoir. It also has temperature resistance and excellent stability, and can effectively plug leaks in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of temporary plugging, and discloses an oil and gas layer protective agent using high-performance resin and fiber as raw materials and a preparation method thereof, wherein composite fibers are interspersed in a network structure constructed by the resin; the composite fibers include inner fibers and outer fibers, the inner fibers are polyglycolic acid, and the outer fibers are polylactic acid; and / or the composite fibers include inner fibers and outer fibers, the inner fibers are polyglycolic acid, and the outer fibers are polylactic acid@sodium carboxymethyl cellulose; the resin includes: a polymer containing siloxane, or a mixture of a polymer containing siloxane and a polyvinyl alcohol resin. The oil and gas layer protective agent provided by the present invention is used to synergistically improve the plugging efficiency by means of fiber and resin grafting. The resin can fill the gaps between the fibers, and the fibers can improve the stability of the resin, thereby achieving the dual purposes of plugging and filling the leak at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of temporary plugging, in particular to an oil and gas layer protective agent using high-performance resin and fiber as raw materials and a preparation method thereof. Background Art

[0002] During drilling, after the reservoir is drilled, due to the existence of positive pressure difference, solid particles in the drilling fluid enter the formation through the pores. The solid particles will cause permanent damage to the reservoir. Therefore, the commonly used method is to use shielding temporary plugging technology to protect the oil and gas layer.

[0003] In the currently commonly used temporary plugging technology, bridging particles, filling particles, and variable particles are added to fill the pores of the formation step by step under the action of positive pressure difference to achieve the purpose of plugging. Among the existing particles, calcium carbonate particles (rigid particles) are commonly used. Specifically, the purpose of improving plugging is achieved by grading calcium carbonate particles of different mesh sizes. However, the plugging effect is limited because although rigid particles can plug the oil and gas layers under the action of positive pressure difference, they cannot penetrate deep into the pore throat for plugging in harsh environments, and if they enter the deep pore throat, their own rigidity can easily cause damage to the reservoir. At present, fiber fillers are also used for filling, but although fiber fillers can enter the deep pore throat through stacking, there are still gaps in the network structure formed by stacking, which results in low improvement in the plugging effect. Summary of the invention

[0004] Technical problems solved by the present invention:

[0005] It is used to solve the problem that the blocking effect improvement in the prior art is limited.

[0006] The technical solution adopted by the present invention is:

[0007] In view of the above technical problems, the object of the present invention is to provide an oil and gas layer protective agent using high-performance resin and fiber as raw materials and a preparation method thereof.

[0008] Based on this, the specific implementation plan is:

[0009] An oil and gas layer protective agent made of high-performance resin and fiber, in which composite fiber is interspersed in a network structure constructed by resin;

[0010] The composite fiber includes at least one of (1-1) to (1-2):

[0011] (1-1) The composite fiber comprises an inner fiber and an outer fiber, wherein the inner fiber is polyglycolic acid and the outer fiber is polylactic acid;

[0012] (1-2) The composite fiber comprises an inner fiber and an outer fiber, wherein the inner fiber is polyglycolic acid and the outer fiber is polylactic acid@sodium carboxymethyl cellulose;

[0013] The resin includes: a polymer containing siloxane, or a polymer containing siloxane and a polyvinyl alcohol resin.

[0014] The composite fiber includes an inner fiber and an outer fiber. Specifically, the inner fiber is polyglycolic acid, and the outer fiber is polylactic acid@sodium carboxymethyl cellulose.

[0015] In the present invention, the inner fiber and the outer fiber are coaxially arranged, and the specific method is:

[0016] (1) polyglycolic acid is dissolved in a solvent and dissolved by ultrasonication to obtain a first spinning solution;

[0017] (2) Polylactic acid @ sodium carboxymethyl cellulose is dissolved in a solvent, and after ultrasonic dissolution, a second spinning solution is obtained. The preparation method of the polylactic acid @ sodium carboxymethyl cellulose mentioned above is: sodium carboxymethyl cellulose is dissolved in hot water to obtain a 3wt% sodium carboxymethyl cellulose aqueous solution for use; the sodium carboxymethyl cellulose aqueous solution and the PEG400 aqueous solution (volume ratio of 1:10) are blended (100°C water bath for 2h), and then KH550 is added for blending and stirring, and then dried to obtain modified sodium carboxymethyl cellulose, which is then melt-blended with polylactic acid (PLA) to obtain polylactic acid @ sodium carboxymethyl cellulose. The above-mentioned drying and melt blending can be carried out by conventional operations in the art. The mass ratio of the above-mentioned sodium carboxymethyl cellulose, PEG400, KH550, and polylactic acid is 1:0.5:0.3:5.

[0018] In (1) to (2), the solvent is the same, and specifically at least one of N,N-dimethylformamide, tetrahydrofuran, ethanol, methanol, and chloroform can be selected. At the same time, the concentration of the spinning solution is controlled to be 10% (w / v). In addition, other commonly used concentration values ​​of the spinning solution can also be used.

[0019] (3) Injecting the first spinning solution and the second spinning solution into a syringe, performing electrospinning to obtain a spun body, and removing the non-volatile solvent; the electrospinning parameters are: voltage 18 kV, receiving distance 18 cm, temperature 20-25 ° C, humidity 34-36%, and time 3 h.

[0020] (4) calcining the spunbond (using a muffle furnace and heating from room temperature to 280°C at a heating rate of 1.8°C / min and maintaining the temperature for 1.5 h) to obtain a composite fiber;

[0021] (5) The composite fiber was immersed in a 2 mg / ml dopamine solution. The preparation method of the dopamine solution was as follows: dopamine was dissolved in Tirs-HCl buffer (pH = 8.0) and immersed at 25-30 ° C for 5-8 h to obtain dopamine-modified composite fibers; the mass ratio of the composite fiber to dopamine was 1:0.08.

[0022] (6) Vinyl triethoxysilane, acrylic acid, acrylamide, an initiator (azobisisobutyronitrile), and a solvent (ethanol) are uniformly blended, and then reacted at 70-90°C for 3-7 hours under a nitrogen atmosphere to obtain a polymer; the molar ratio of vinyl triethoxysilane, acrylic acid, and acrylamide is 1:1-3:1-3. The amount of azobisisobutyronitrile added accounts for 2-3wt% of the total amount of the aforementioned additives.

[0023] (7) After the polymer, dopamine-modified composite fiber, and polyvinyl alcohol are formed into dispersions respectively, they are blended, and the polyvinyl alcohol is dissolved in 90°C water. The above-mentioned blended liquid is heated, and then boric acid is added thereto, and the product is cooled and collected, and then dried to obtain a composite fiber-resin. In the above, the mass ratio of the polymer, dopamine-modified composite fiber, and polyvinyl alcohol is 1:0.7~1.5:0.8~1.2, and the boric acid is added to 5wt% of the mass of polyvinyl alcohol. The polymer aqueous dispersion is 8~15wt%, the dopamine-modified composite fiber aqueous dispersion is 1~5wt%, and the polyvinyl alcohol aqueous dispersion is 7~15wt%.

[0024] The technical mechanism and beneficial effects adopted by the present invention are as follows:

[0025] (1) The oil and gas layer protective agent provided by the present invention is a composite fiber-resin, which can effectively reduce penetration and damage to the reservoir, and also has the advantages of temperature resistance and excellent stability.

[0026] (2) The oil and gas layer protective agent provided by the present invention is used to achieve synergistic improvement of plugging efficiency by grafting fibers and resins. The resin can fill the pores between the fibers, and the fibers can improve the stability of the resin, thereby achieving the dual purposes of plugging and filling the leakage at the same time.

[0027] (3) The oil and gas layer protective agent provided by the present invention is in the form of an inner and outer layer composite fiber, with polyglycolic acid as the inner layer and polylactic acid-sodium carboxymethyl cellulose as the outer layer. The inner and outer layer form can regulate the degradation rate of the fiber, thereby avoiding affecting subsequent mining work. The introduction of sodium carboxymethyl cellulose can improve the toughness of polylactic acid; in addition, sodium carboxymethyl cellulose is modified by polyethylene glycol and a coupling agent and then added to polylactic acid, which can improve the mechanical properties of polylactic acid and avoid incompatibility.

[0028] (4) The oil and gas layer protective agent provided by the present invention introduces active sites by introducing dopamine, which is beneficial to the bonding between the fiber and the resin.

[0029] (5) The oil and gas layer protective agent provided by the present invention comprises a resin including polysiloxane and polyvinyl alcohol, and a small amount of boric acid is introduced to prepare the composite. By introducing siloxane, the purpose of improving stability is achieved, which can be reflected in the stability of the siloxane structure (that is, the bond energy of silicon and oxygen is high). DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0031] Example 1

[0032] This embodiment provides a method for preparing an oil and gas layer protective agent, comprising the following steps:

[0033] 1. Preparation of composite fibers

[0034] (1) The first spinning solution is prepared by dissolving polyglycolic acid in chloroform and mixing the solution by ultrasonic mixing.

[0035] (2) Second spinning solution: Sodium carboxymethyl cellulose is dissolved in hot water to obtain a 3wt% sodium carboxymethyl cellulose aqueous solution for standby use; the sodium carboxymethyl cellulose aqueous solution is blended with the PEG400 aqueous solution, the volume ratio of PEG400 to water is 1:10, and the blending treatment is treated in a water bath at 100°C for 2h. Then, KH550 is added for blending and stirring, and then the modified sodium carboxymethyl cellulose is obtained by drying, and then the modified sodium carboxymethyl cellulose is melt-blended with polylactic acid to obtain polylactic acid @ sodium carboxymethyl cellulose. Drying and melt blending can be performed by conventional operations in the art. The mass ratio of the aforementioned sodium carboxymethyl cellulose, PEG400, KH550, and polylactic acid is 1:0.5:0.3:5. The obtained polylactic acid @ sodium carboxymethyl cellulose is then dissolved in chloroform and ultrasonically blended to obtain the second spinning solution.

[0036] (3) 10% (w / v) of the first spinning solution and 10% (w / v) of the second spinning solution were respectively injected into a needle syringe, and the coaxial spinning technology was adopted. The first spinning solution was used as the inner spinning solution, and the second spinning solution was used as the outer spinning solution for injection. The injection ratio of the inner and outer layers was 2:1, wherein: voltage was 18 kV, receiving distance was 18 cm, temperature was 20-25 °C, humidity was 34-36%, and time was 3 h. After the spinning was completed, it was placed in a muffle furnace for calcination. The temperature was raised from room temperature to 280 °C at a heating rate of 1.8 °C / min and kept warm for 1.5 h to obtain a composite fiber.

[0037] 2. Preparation of fiber-resin

[0038] (1) 11.4 g of vinyl triethoxysilane, 8.7 g of acrylic acid, 8.6 g of acrylamide, 0.6 g of azobisisobutyronitrile, and 200 g of ethanol were uniformly mixed and reacted at 90° C. for 5 h under a nitrogen atmosphere to obtain a polymer.

[0039] (2) The composite fiber was immersed in a 2 mg / ml dopamine solution (dopamine was dissolved in 10 mM Tris-HCl buffer, pH = 8.0), the mass ratio of the composite fiber to dopamine was 1:0.08, the immersion was carried out at 25-30 °C, the time was controlled within 5 h, and the dopamine-modified composite fiber was obtained after filtration, multiple washing and drying.

[0040] (3) A 10 wt% polymer aqueous dispersion, a 3 wt% dopamine-modified composite fiber aqueous dispersion, and a 10 wt% polyvinyl alcohol aqueous dispersion are formed respectively, and the ratio of the added polymer, dopamine-modified composite fiber, and polyvinyl alcohol is 1:1.2:1. After mixing, the mixture is heated at 70°C for 3 h, and then 5 wt% of boric acid by mass of the polyvinyl alcohol is added. The mixture is stirred for 0.5 h, cooled to room temperature, washed, and dried to obtain the fiber-resin.

[0041] Comparative Example 1

[0042] The difference between this comparative example and Example 1 is that the fiber-resin is replaced by a composite fiber.

[0043] Comparative Example 2

[0044] The difference between this comparative example and Example 1 is that the fiber-resin is replaced by a composite fiber and a resin blend.

[0045] Comparative Example 3

[0046] The difference between this comparative example and Example 1 is that the fiber-resin is replaced by fiber-polyvinyl alcohol resin.

[0047] Test example

[0048] 1. Determination of fiber degradation rate

[0049] The composite fiber in Example 1 and control group 1: polyglycolic acid-polylactic acid fiber (polylactic acid@sodium carboxymethyl cellulose in the composite fiber in Example 1 was replaced by polylactic acid) were used as samples for measurement. The measurement was carried out with reference to ISO13781-2017 (using the weight loss method, simulating a temperature of 70°C), and the tensile strength of the fiber was measured with reference to GB / T 14344-2008. The results are shown in Table 1.

[0050] Table 1 Measurement results

[0051]

[0052] 2. Plugging performance determination

[0053] The samples of Example 1 and Comparative Examples 1-3 were used for the test. The breakthrough pressure was measured using a core flow tester using an artificial filling core method. The test was conducted in a dispersed state. The samples were filled into an artificial core mold, pressurized to 5 MPa with a pressure pump and held for 24 hours. The breakthrough pressures were then measured using advection avalanche. The results are shown in Table 2.

[0054] Table 2 Measurement results

[0055]

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An oil and gas layer protective agent using high-performance resin and fiber as raw materials, characterized in that: The composite fibers are interspersed in the network structure constructed by the resin; The composite fiber includes at least one of (1-1) to (1-2): (1-1) The composite fiber comprises an inner fiber and an outer fiber, wherein the inner fiber is polyglycolic acid and the outer fiber is polylactic acid; (1-2) The composite fiber comprises an inner fiber and an outer fiber, wherein the inner fiber is polyglycolic acid and the outer fiber is polylactic acid-sodium carboxymethyl cellulose; The resin includes: a polymer containing siloxane, or a polymer containing siloxane and a polyvinyl alcohol resin; The preparation method of the composite fiber comprises the following steps: preparing polyglycolic acid, polylactic acid or polylactic acid-sodium carboxymethyl cellulose to obtain spinning solutions, and subjecting the spinning solutions to electrostatic spinning and calcination to obtain the composite fiber; The preparation method of polylactic acid-sodium carboxymethyl cellulose comprises the following steps: mixing a sodium carboxymethyl cellulose aqueous solution with a PEG400 aqueous solution, adding KH550 for blending and stirring, drying to obtain modified sodium carboxymethyl cellulose, and then melt-blending the modified sodium carboxymethyl cellulose with polylactic acid to obtain polylactic acid-sodium carboxymethyl cellulose; The preparation method of the oil and gas layer protective agent comprises the following steps: S1 composite fiber is modified by dopamine to obtain dopamine-modified composite fiber; S2 vinyl triethoxysilane, acrylic acid, acrylamide, initiator and solvent are mixed and reacted under an inert atmosphere to obtain a polymer; S3: heating the polymer, dopamine-modified composite fiber and polyvinyl alcohol in a solvent system, adding boric acid, filtering and drying to obtain an oil and gas layer protective agent.

2. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: The parameters of electrospinning were: voltage 18 kV, receiving distance 18 cm, temperature 20-25 °C, humidity 34-36%, and time 3 h.

3. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: Calcination: Heat from room temperature to 280°C at a heating rate of 1.8°C / min and keep at this temperature for 1.5h.

4. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: Blending treatment: 100℃ water bath for 2h.

5. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: The mass ratio of sodium carboxymethyl cellulose, PEG400, KH550 and polylactic acid is 1:0.5:0.3:

5.

6. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: The composite fiber was immersed in dopamine solution and reacted at 25-30°C for 5 hours.

7. The oil and gas layer protective agent with high-performance resin and fiber as raw materials according to claim 1, characterized in that: The ratio of polymer, dopamine-modified composite fiber and polyvinyl alcohol is 1:0.7~1.5:0.8~1.2, and the added amount of boric acid accounts for 5wt% of polyvinyl alcohol.

Citation Information

Patent Citations

  • Preparation method of modified cellulose / polylactic-acid nanometer fiber composite film used for heavy-metal ions to adsorb

    CN102605555A

  • polyvinyl alcohol (PVA) / sodium carboxy methylated cellulose (Na-CMC) nanofiber, preparation method and application

    CN102943318A